Accounting Flexibility and Managers’ Forecast Behavior Prior to Seasoned Equity Offerings - KIM, Jae Bum (Institutional Knowledge at Singapore Management University, 2012)
This study examines the effect of accounting flexibility on managers’ forecasting behavior prior to seasoned equity offerings(SEO). While SEO firms have strong incentives to convey optimistic information to boost the pre-SEO stock price, they also face enhanced litigation risk arising from SEO-related regulations. Thus, I hypothesize that managers of SEO firms will release optimistic forecasts prior to an SEO only if they have the accounting flexibility to manage subsequent reported earnings to meet or exceed their forecasts. I find that managers with greater accounting flexibility are more likely to issue a forecast prior to the SEO and their forecasts are more optimistic and more specific. Further, I find that accounting flexibility has no effect on managers’ forecasting behavior either for non-SEO control firms or for non-SEO periods. My results suggest that, when managers face a tension between incentives to report optimistically and high litigation risk, accounting flexibility is an important factor that determines their forecasting behavior.